PENINGKATAN HASIL BELAJAR IPS MODEL MENGGUNAKAN MODEL COOPERATIVE LEARNING TIPE TEAM GAME TOURNAMENT (TGT) DI KELAS V SEKOLAH DASAR - Mailiati, Yulia; Indrawati, Tin; Nasrul, Nasrul (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2018)
AbstractThe purpose of this research  was to describe the improvement of results of IPS students use the model of Cooperative Learning type Team Game Tournament (TGT) grade V SDN Negeri 10 Bandar Buat,  Padang city. This type of Research is classroom action Research by using qualitative and quantitative approaches. The Research subject is the teacher (practitioner) and 27 students. The results showed an increase from cycle I to cycle II by the: a) planning 9%, b) implementation, aspects of the teacher and aspects of students amounted to 17.9%, and c) student learning outcomes amounting to 25.9%. Thus, the application of model Cooperative Larning type Team Game Tournament (TGT) can improve student learning outcomes in learning IPS at class V SDN 10 Bandar Buat, kota Padang   Keywords : Learning Outcomes, Learning social studies, TGT